Financial Control as Soft Repression: The Islamic Civil Society in France Reacting to 2021’s Law Against Separatism - la Forgia, Enrico Maria (PARTECIPAZIONE E CONFLITTO, 2026)
After Daesh terrorist attacks, the French State reinforced its securitarian policies, targeting – among others - Muslim associations (Kaya, 2011). The “War on Terror” has been accompanied by restrictions on civil liberties in the name of rapid and preventive repression (Vedaschi & Graziani, 2019). Yet repression does not operate solely through visible coercion. Alongside the use of force, authorities deploy less visible strategies aimed at weakening Civil Society organizations (Talpin, 2016). Among these, financial control constitutes a central mechanism of soft repression, understood as a non-violent form of repression that reduces the capacity for contestation available to subaltern actors. In France, where the non-profit sector is largely dependent on public funding (Archambault et al., 2013), the State can use budgetary resources as leverage. Authorities often mobilize discourses of “budgetary constraint” to pressure organizations into compliance or to fragment mobilization by fostering competition over scarce funds (Talpin & Bonneville, 2023). In extreme cases, security-related justifications are invoked to freeze organizations’ bank accounts, like after the introduction of the Law Against Separatism (2021) – later renamed Law Concerning the Respect of Republican Principles. Drawing on qualitative interviews with leaders of four Muslim associations, this paper addresses the following research questions: How and when does the French State enact soft repression through financial control over Muslim associations? How do targeted associations react? By analyzing both State strategies and the responses of affected organizations, before and after 2021’s law, the paper highlights how soft repression is deployed and when it prompts adaptive, infrapolitical, reactions by Muslim associations.